The Social Acceptance Factors for Insulation Boards Produced With CO2-Derived Foam - Simons , Lisanne; Ziefle , Martina; Arning, Katrin (Frontiers in Energy Research, 2021)
The negative consequence of increased greenhouse gas emissions have incited research to focus on developing sustainable technologies to reduce the use of fossil raw material. Carbon Capture and Utilization is such a technology. It reuses captured CO2 as raw material for the production of salable products. Beyond their technical and economic feasibility, the acceptance of these products is vital for the successful roll-out of the technology. The two-step empirical study—a qualitative preliminary study (n = 8 experts, n = 16 laypeople) and a quantitative survey study (N = 643)—described in the present paper focused on the acceptance of insulation boards produced by means of CCU by its potential Dutch and German consumers. The study aimed to quantify the level of public acceptance of the product, to identify perceived (dis)advantages, and to pinpoint the drivers behind the acceptance. In the survey, respondents evaluated cognitive and affective acceptance factors, as well as the acceptance of the use of plastic in the product. The results showed that the respondents had little knowledge on CCU, but that CCU insulation boards were nevertheless accepted rather than rejected, with the benefit perception being the common predictor for the three acceptance measures. Public communication and policy should address the product’s (environmental) benefits and foster an increase in the public awareness of the technology.